Legal Certainty in Underground Space Utilization: Lessons from Selected Jurisdictions - Ghary Delia Handojo; Ariawan Gunadi (Contrarius Indonesia, 2026)
Rapid urbanization, population growth, infrastructure expansion, and land scarcity have encouraged underground space utilization for urban development. However, Indonesia lacks a comprehensive legal framework regulating underground space ownership, utilization, and registration, creating legal uncertainty regarding rights allocation and subsurface development. This study examines the legal challenges and regulatory deficiencies associated with underground space utilization in Indonesia and formulates legal reform recommendations by drawing lessons from comparative legal systems. The study employs normative legal research using statutory, conceptual, and comparative approaches. The analysis focuses on existing Indonesian regulations and evaluates legal arrangements governing underground space in Japan, England, and Germany. The study finds that Indonesia has not established a specific and integrated legal regime capable of regulating underground space utilization effectively. The absence of clear legal provisions has limited legal certainty and hindered the implementation of sustainable underground development. Therefore, this study proposes legal reform through the clarification of vertical property boundaries, the recognition of independent underground space rights, the development of a three-dimensional land registration system, and the harmonization of related legislation. These measures can strengthen legal certainty, improve land governance, and support sustainable urban development in Indonesia.